A COMPARATIVE STUDY OF EMPLOYEE ENGAGEMENT IN PRIVATE AND PUBLIC COMPANIES IN OMAN OIL AND GAS SECTOR - PORKODI, S (JOURNAL OF RESEARCH IN MANAGEMENT, 2019)
The oil boom in the Arabian Peninsula has removed Oman's dependence from the agriculture sector and shifted to the oil and gas sector. Oman's economy is dependent on the public sector but the expanding population has made it inevitable to penetrate deeper into the private sector too. This present research study attempts to compare employee engagement in public and private companies in Oman oil and gas sector. It aims to identify the difference that exist in the comprehension of employee engagement. Add to that, this study also aims to compare cognitive, emotional and behavioral levels of employee engagement in the said sectors. Primary data was sourced through structured questionnaire and the information regarding the respondents were collected from 140 respondents. Out of that 70 respondents in public and 70 respondents in private Oil and Gas sector. Snowball sampling method was used to collect the data. The target respondent for this study are middle level employees. The outcome revealed that there is no significant difference in behavioural level of employee engagement but cognitive and emotional level there are some significant differences in employee engagement between public and private companies in oil and gas sector.